Comparison of Clinical Outcomes and Fever Clearance Time with Azithromycin versus Doxycycline in Paediatrics Scrub Typhus - Anita Riang Simon; Sowjan Manohar; V Manigandan; S. M. Kiruthikadevi; B Sathyamurthy; M Valarmathi (Annals of African Medicine, 2026)
Abstract Background: Scrub Typhus is an important cause of acute febrile illness in children in endemic regions, often presenting with nonspecific clinical features that delay diagnosis. Early initiation of appropriate antibiotic therapy is critical in reducing morbidity and preventing complications. Doxycycline has traditionally been the drug of choice; however, Azithromycin is increasingly used in Paediatric populations due to safety considerations, especially in younger children. Comparative evidence evaluating clinical outcomes and fever clearance time between these two agents in children remains limited. Objective: To compare clinical outcomes and fever clearance time in Paediatric patients with Scrub Typhus treated with Azithromycin versus Doxycycline. Materials and Methods: This retrospective observational study was conducted over 6 years from January 2020 to January 2026 at Tertiary Care Centre in Chengalpattu. Paediatrics patients aged 1-18 years with serologically confirmed Scrub Typhus were included. Patients were categorized into two groups based on the antibiotic administered: Azithromycin and Doxycycline. Baseline demographic, clinical, and laboratory parameters were recorded. The primary outcome was fever clearance time, defined as the time from initiation of antibiotic therapy to sustained defervescence. Secondary outcomes included duration of hospital stay, time to clinical improvement, complication rates, need for intensive care, and mortality. Statistical analysis was performed using appropriate tests, with P < 0.05 considered statistically significant. Results: A total of 120 Paediatric patients were included, with 60 patients in each treatment group. Baseline characteristics were comparable between the groups. The Doxycycline group demonstrated a significantly shorter fever clearance time compared to the Azithromycin group. Patients receiving Doxycycline also had a reduced duration of hospital stay and faster overall clinical improvement. Complication rates, including respiratory, neurological, and hepatic involvement, were similar between the two groups. Intensive care requirements and mortality rates did not differ significantly. Conclusion: Both Azithromycin and Doxycycline are effective in the treatment of Paediatric Scrub Typhus. However, Doxycycline is associated with faster fever resolution and earlier recovery. Azithromycin remains a valuable alternative, particularly in younger children or where Doxycycline use is limited. Early diagnosis and prompt initiation of therapy are essential for improving outcomes.